#TITLE_ALTERNATIVE# - AYUNDA ZIDAFRIAN (NIM : 10209010),
The increase need of geothermal energy as the alternative energy source result in the need of exploring new geothermal sources area. One of the geophysics method that can be used as the first geothermal investigation is gravity method. The gravity value was measured in 370 points in the “DNG” area and followed by the data processing until the Complete Anomaly Bouguer value obtained. The following process was separating the regional part that shows density anomaly of the deeper source and residual part that shows density anomaly of the shallower source. The results then transformend into a contour map to be interpreted. The spectral analysis can be used to investigate the depth of both regional and residual part. Modelling and inversion then applied to the residual data. The results obtained show that the high density anomaly dominating the central part of the study area and associated with the presence of volcano in the study area.